2014
DOI: 10.1111/asj.12278
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors creating consumer attributes of roasted beef steaks

Abstract: The aim of the study was to analyze the factors creating consumer attributes of roasted beef steaks of various animals. Eight cuts from 30 carcasses (characterized by various types of animal, conformation and fat class, rib fat thickness, ossification score) were selected. Samples were prepared using the roasting method and consumers rated the tenderness, juiciness, flavor, overall acceptability (rated in a 100-point scale), and satisfaction (rated from 2 to 5) for analyzed samples. No influence of type of ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In contrast, incorporating the USDA marbling score into the prediction model of juiciness or tenderness was more appropriate than incorporating the European conformation score and the European fat score. Also in our previous study, it was observed that the quality of beef meat from crossbreeding depended on the cut and thermal treatment (Guzek et al 2015b).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, incorporating the USDA marbling score into the prediction model of juiciness or tenderness was more appropriate than incorporating the European conformation score and the European fat score. Also in our previous study, it was observed that the quality of beef meat from crossbreeding depended on the cut and thermal treatment (Guzek et al 2015b).…”
Section: Discussionmentioning
confidence: 88%
“…As a result of these larger efforts of many various stakeholders, in the half-year 2013 Australia's beef production was 2.2 million tonnes, while export recorded nearly 1.5 million tonnes, thus making Australia the 5th most important producer and the 3rd most important exporter of beef in the world (USDA 2013). Since the MSA System turned out to be so profitable to Australian beef production, the system's elements may be instituted in other countries, such as the MQ4 score which was tested in Poland in the research presented previously (Guzek et al 2015a(Guzek et al , 2015b. However, it must be emphasised that consumers from various countries may have different beef perception , thus the applied criteria cannot be transferred directly to another country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSA model has been tested successfully in different countries (reviewed by Bonny et al, (2018) [35]) including France [36][37][38], South Korea [39], Northern Ireland [40][41][42][43], the USA [44,45], Japan [46], Ireland [47], South Africa [48], New Zealand [49], and Poland [50,51]. The general conclusion is that the MSA methodology is relevant in all these countries, indicating that the MSA model is likely to be generally applicable.…”
Section: Modelling Approaches Combining Different Quality Indicators mentioning
confidence: 99%
“…The Meat Standards Australia (MSA) system, which is also based on muscle type, is more accurate as it takes into account other factors from the farm to the plate (cooking method) through the slaughterhouse (carcase weight, animal maturity, pH, marbling, etc) and the retailer (ageing time). It was successfully tested in different countries (Hocquette et al 2014;Guzek et al 2015;Henchion et al 2017), such as in Asia (South Korea, Japan), North America (USA), New Zealand, South Africa and also Europe (Northern Ireland, Poland and the Republic of Ireland), and particularly in France with French meat and French consumers (Legrand et al 2013(Legrand et al , 2017. Further developing the current star system, that is, to move towards a system comparable to the MSA model would make it possible to identify the best combinations, that is, between the animal, muscle, duration of maturation, and cooking method.…”
Section: Willingness To Pay For Better Beefmentioning
confidence: 99%